1981
DOI: 10.1056/nejm198110293051807
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Hepatitis B Virus DNA into the Genome of Liver Cells in Chronic Liver Disease and Hepatocellular Carcinoma

Abstract: We used recombinant-DNA technology and gel electrophoresis to find hepatitis B virus DNA (HBV-DNA) in liver and tumor tissue from patients with hepatocellular carcinoma and chronic liver disease, and to study the integration of HBV-DNA into the genome of these tissues' cells. In 12 patients with hepatocellular carcinoma who had hepatitis B surface antigen (HBsAg) in their serum, integrated HBV-DNA was identified in the tumors; it was also found in tumors from three of eight patients who were seronegative for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
282
3
4

Year Published

1984
1984
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 667 publications
(303 citation statements)
references
References 17 publications
14
282
3
4
Order By: Relevance
“…This demonstrates that M6P͞IGF2R allele inactivation occurs early rather than late in the pathogenesis of liver tumors. Cirrhotic nodules have generally been regarded as hyperplastic regenerative lesions, but some also arise by clonal expansion (23)(24)(25). Therefore, we questioned whether the cirrhotic nodules adjacent to dysplastic lesions and HCCs had M6P͞IGF2R allele loss, a genetic change observable only if the cirrhotic nodules were of clonal origin (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that M6P͞IGF2R allele inactivation occurs early rather than late in the pathogenesis of liver tumors. Cirrhotic nodules have generally been regarded as hyperplastic regenerative lesions, but some also arise by clonal expansion (23)(24)(25). Therefore, we questioned whether the cirrhotic nodules adjacent to dysplastic lesions and HCCs had M6P͞IGF2R allele loss, a genetic change observable only if the cirrhotic nodules were of clonal origin (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective study in Taiwan has indicated a relative risk of over 200 with all but one case occurring among persons who were carriers prior to development of HCC (Beasley et al, 1981) while viral DNA has been found incorporated into the host genome of HCC patients (Shafritz et al, 1981) including those who have no viral markers of HBV infection (Brechot et al, 1982). 1t has also been suggested that chronic HBV infection acting alone could be responsible for the large range of incidence for HCC that exists between different countries and that aflatoxin has little carcinogenic effect on humans (Prince, 1978;Lutwick, 1979). This hypothesis was based on broad geographical comparisons of the two diseases and on estimation of a similar risk for HCC among carriers of HBV in Mozambique and in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the majority ([75%) of cirrhosis complications and HCC occur after HBeAg seroconversion in this population [10]. Moreover, HBV can cause HCC even in patients who do not develop cirrhosis [11].…”
Section: Importance Of Age Of Acquisition Of the Virusmentioning
confidence: 96%